METHODICAL RECOMMENDATIONS FOR PASSING THE "DIGITAL WORLD" TOPIC IN 6TH SYMPHONY LANGUAGE CLASSES - Maxkamova Guluzroxon Abdumutalibovna (Journal of Learning on History and Social Sciences, 2024)
This article describes methodological recommendations for the organization of 6th grade mother tongue lessons from new generation textbooks based on the National Curriculum.